2003
DOI: 10.1046/j.1600-6135.2003.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Old-for-Old Kidney Allocation Allows Successful Expansion of the Donor and Recipient Pool

Abstract: Allocation of kidneys from donors older than 64 years to recipients older than 64 years was started in 1999 to improve use of older donor kidneys. Kidneys are allocated locally without HLA-matching to keep cold ischemia short.We compared survival and rejection rates in elderly patients allocated in the old-for-old program (ESP) to patients aged 60 years and older based on HLA-matching, expected ischemia and waiting time (ETKAS).The 69 ESP patients were older (67.9 ± ± 2.5 vs. 63.9 ± ± 2.9 years), had older don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
2
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 15 publications
(13 reference statements)
1
71
2
5
Order By: Relevance
“…A similar model, aimed at increasing the utilization of older donors and reducing waiting time for older recipients, is already being used in the voluntary Eurotransplant Senior Program (23). Early results indicated that the program had potential to meet these goals, particularly in conjunction with reduced cold ischemic time (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar model, aimed at increasing the utilization of older donors and reducing waiting time for older recipients, is already being used in the voluntary Eurotransplant Senior Program (23). Early results indicated that the program had potential to meet these goals, particularly in conjunction with reduced cold ischemic time (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, black patients, who have decreased mortality rates on dialysis, seem to have increased benefit when they are selective regarding organ quality. Despite this, black patients historically have listed more frequently for and received lower quality deceased donor organs relative to white patients (24). Certainly, in addition to life expectancy calculations, patient affinity for dialysis and quality of life are important considerations.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is controversy regarding the outcomes with older kidneys. 7,15,16 Donor age was significantly higher in our older recipients. We analyzed the outcome of our elderly patients according to donor's age and failed to observe a significant difference in actuarial patient and graft survivals when comparing older recipients of kidneys from an aging donor.…”
Section: Discussionmentioning
confidence: 67%
“…Donor HLA-typing is not required, so allocation is done by using only ABO group matching, negative crossmatch,and a local allocation based on waiting time in order to keep cold ischemia time to a minimum. In the preliminary report by Fritsche et al [74], this policy allowed the expansion of the donor and recipient pools without significantly affecting patient and graft survival. Anyway an increase in rate of acute rejections due to a higher number of HLA mismatches causing longer hospitalization and a major risk of graft loss was recorded.…”
Section: Strategy To Optimize the Outcome Of Marginal Donors And Kidnmentioning
confidence: 99%